Expanding the spectrum of NUS1-related progressive myoclonic epilepsy: a novel variant and exploratory use of metformin - Sau, Cristina; López-Rodríguez, Sergi; Falip, Mercè; Esteve-Garcia, Anna; Sala-Padró, Jacint; Aguilera, Cinthia; Navarro-Romero, Alba; Lasa-Aranzasti, Amaia; Rodríguez-Bel, Laura; Hernández-Pérez, Guillermo (Frontiers in Genetics, 2025)
IntroductionProgressive myoclonic epilepsies (PME) are rare genetic disorders typically presenting with myoclonus, seizures, and cognitive decline. While several genes are associated with PME, the NUS1 gene has recently emerged as a potential cause. We report the case of a 41-year-old woman who presented with tics, myoclonus, and language difficulties followed by gait instability, tremor, absence seizures, and psychotic symptoms including persistent hallucinations and delusional misidentification.MethodsNeurology and psychiatry specialists reviewed clinical data. Brain MRI, scalp video-EEG monitoring, and [18F]-FDG-PET/MRI were performed following standardized protocols. Whole exome sequencing (WES) guided by human phenotype ontology (HPO) terms was performed, and variants were interpreted according to American College of Medical Genetics and Genomics (ACMG) guidelines. Additionally, we conducted a review of previously reported cases of NUS1 pathogenic/likely pathogenic variants associated with PME to better characterize the clinical and paraclinical features and to explore potential management strategies.ResultsA novel heterozygous frameshift likely pathogenic variant in the NUS1 gene, c.248del, p. (His83Profs*22), was identified in the patient. This finding led to the introduction of a targeted therapeutic strategy, including the initiation of metformin and a thorough revision of the patient’s existing psychiatric treatment. The patient showed an improvement in her psychiatric manifestations. However, neurological examination revealed either stable or slightly worsened signs, and she did not achieve seizure freedom.DiscussionThis is the first review of NUS1 from a PME perspective and the first report describing the exploratory use of metformin as a potential therapeutic intervention. In our case, metformin was introduced simultaneously with a change in antipsychotic treatment, so its specific clinical impact cannot be determined. Additional studies are needed to improve understanding of the benefits of using metformin and other therapeutic strategies in NUS1-related disorders. Further studies are essential to clarify the full phenotypic spectrum associated with NUS1 variants and to improve our understanding of how specific variant types and locations contribute to clinical presentation.